1996
DOI: 10.1063/1.117911
|View full text |Cite
|
Sign up to set email alerts
|

Surface morphology and growth mechanism of YBa2Cu3O7−y films by metalorganic chemical vapor deposition using liquid sources

Abstract: We have investigated surface morphology of YBa2Cu3O7−y thin films prepared by chemical vapor deposition (CVD) using liquid metalorganic (MO) sources on MgO(100) single crystalline substrates by atomic force microscopy (AFM). An abrupt change in the terrace width was observed at the deposition temperature of around 750 °C. An anomalous decrease in the efficiency of incorporation of the yttrium component into the film was also found above the same temperature. It suggests that the appearance of liquid phase on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(14 citation statements)
references
References 5 publications
(5 reference statements)
1
13
0
Order By: Relevance
“…Solid source precursors, while easy to handle, are prone to sintering, which progressively lowers the surface area (for this type of precursor, deposition is typically diffusion-limited) and gives rise to time- dependent volatilization rates. In contrast, liquid precursors have a constant surface area that provides stable precursor delivery. A Cd(hfa) 2 (TMEDA) analogue with a lower melting point would be highly desirable if it were a liquid at standard MOCVD growth reactor-operating temperatures, while maintaining robust thermal properties. It is well-established that appropriate substitutions at the ligand periphery can be used to tailor melting points in related types of Group II precursors without deleterious impact on volatility or thermal stability. , Complementary approaches to low-melting cadmium precursors have very recently been reported. ,
…”
Section: Introductionmentioning
confidence: 99%
“…Solid source precursors, while easy to handle, are prone to sintering, which progressively lowers the surface area (for this type of precursor, deposition is typically diffusion-limited) and gives rise to time- dependent volatilization rates. In contrast, liquid precursors have a constant surface area that provides stable precursor delivery. A Cd(hfa) 2 (TMEDA) analogue with a lower melting point would be highly desirable if it were a liquid at standard MOCVD growth reactor-operating temperatures, while maintaining robust thermal properties. It is well-established that appropriate substitutions at the ligand periphery can be used to tailor melting points in related types of Group II precursors without deleterious impact on volatility or thermal stability. , Complementary approaches to low-melting cadmium precursors have very recently been reported. ,
…”
Section: Introductionmentioning
confidence: 99%
“…These groups clarified that the LPE could achieve an excellent crystallinity and a quasi-atomically flat surface. On the other hand, Yoshida et al substantiated that the quasi-liquid phase growth was observed in metal organic chemical vapor deposition on an YBa 2 Cu 3 O y (YBCO) thin film [10], just as observed in the vapor-liquid-solid (VLS) growth. Moreover, Yun et al demonstrated that the NdBa 2 Cu 3 O y (NdBCO) thin films fabricated by tri-phase epitaxy using Ba-Cu-O flux which is substantially same with VLS showed a high T c of 94 K which had the surface morphology consisted of flat terraces with a width of $200 nm and a step height of 1.2 nm [11].…”
Section: Introductionmentioning
confidence: 90%
“…For example, an abrupt change in film growth morphology at a specific substrate temperature during MO-CVD has been explained in terms of the formation of a quasi-liquid surface layer at the higher temperatures, leading to a change from conventional vapour growth to something termed vapourliquid-solid growth. 82 This concept has been extended in a technique called tri-phase epitaxy, in which components are supplied to a liquid layer on a growing film surface. 83 Such growth by diffusive transport across a thin liquid flux layer has also been termed hybrid LPE.…”
Section: Chemical Deposition Techniquesmentioning
confidence: 99%